Increasing Trust in Banking and Developing Insurance System for Bank Deposits in Russia - I. V. Dmitriev (Vestnik MGIMO-Universiteta)
In this article the topical issues connected with changes are considered, occurring in the banking sector of Russia, the number of the operating credit organizations caused by essential reduction, intensive revocation of licenses on bank activity at the credit organizations Bank of Russia. According to the author, in this regard there is a number of the problems connected with sufficiency of a network of the operating credit organizations of requirement of ensuring economic growth, formation of the healthy competitive environment, sufficiency of Fund of insurance of deposits for providing guarantees to investors in case of bankruptcy of banks. In article, recent trends of insurance of deposits in the countries of EEC and the USA are considered. Taking into account the revealed tendencies problems of functioning of system of insurance of deposits of citizens in the Russian commercial banks are analyzed. To number of such problems are carried: insufficient volume of an insurance covering; concentration of deposits mainly in the large banks which are on the one hand, carriers of system risk, with another, - in which capitals participates the state, having thus subsidiary responsibility; limited set of functions of Agency and some other. Taking into account the carried-out analysis and an assessment of operating system of insurance of deposits it is offered: to develop the mechanism of overcoming of "moral" risk; increase of financial literacy of the population, in view of activity of some banks on advance in a segment of private investors of the products which aren't covered by system of guaranteeing; to define introduction of the mechanism of differentiation of contributions to the ASV insurance Fund depending on degree of riskiness of activity of participating bank of system, system modernization risk - the focused supervision as bases of stable functioning of the banking sector and its hotel institutes.